Preliminary phytochemical screening of the wild edible plants Passiflora foetida and Buchanania arborescens from Barangays Cabadiangan, Lataban, and Tabla, Liloan, Cebu, Philippines - Asilo, Pamela G. (Department of Biology and Environmental Science, College of Science, University of the Philippines Cebu, 2021)
Wild edible plants (WEPs) are widely collected in different parts of the world. They can be found in various habitats, such as natural forests, agricultural fields, roadsides, and wastelands, and are collected as a source of food, nutrition, and livelihoods. They can thrive in places with difficult geography and harsh climate conditions. WEPs contribute to food security and nutrition as they supply various vegetables, fruits, tubers, and nuts. In developing countries, such as the Philippines, WEPs are very reliable sources of food and nutrients during calamities. They contain diverse flavors and high nutritional content including vitamins, minerals, fiber, phenolic compounds, enzymes, enzyme inhibitors and other bioactive substances. In this study, fruits of wild edible plants Passiflora foetida and Buchanania arborescens were collected, cleansed, and air dried. The collected samples were subjected to oven drying under 55°C for 72 hours. The dried samples were powdered and extracted with different solvents namely, distilled water, ethanol, methanol, hexane, chloroform, and acetone. Then, the plant extracts were qualitatively tested for the presence of flavonoids, tannins, coumarins, cardiac glycosides, anthocyanins, saponins, and phenols. Moisture content and dry matter were also determined by subjecting the plants under 105°C in repeated intervals of heating and weighing until a constant weight was achieved. Presence of tannins, coumarins, cardiac glycosides, saponins, and phenols were detected in the distilled water, methanol, ethanol, and acetone plant extracts of both plants (Passiflora foetida and Buchanania arborescens). The moisture content of Passiflora foetida was approximately 82% while 44% moisture content was found in Buchanania arborescens. Dry matter content was found to be at around 18% in Passiflora foetida and at approximately 56% in Buchanania arborescens. The research showed that the WEPs collected in Liloan, Cebu contain phytochemical compounds relevant to humans. Moreover, higher moisture content is commonly associated with microbial growth while higher dry matter content can be indicative of higher amounts of nutrients and minerals.